Analysis of a measurement scheme for ultrafast hole dynamics by few femtosecond resolution X-ray pump-probe Auger spectroscopy - Cooper,B; Kolorenc,P; Frasinski,LJ; Averbukh,V; Marangos,JP (Faraday Discussions, 2014)
Ultrafast hole dynamics created in molecular systems as a result of sudden ionisation is the focus of much attention in the field of attosecond science. Using the molecule glycine we show through ab initio simulations that the dynamics of a hole, arising from ionisation in the inner valence region, evolves with a timescale appropriate to be measured using X-ray pulses from the current generation of SASE free electron lasers. The examined pump–probe scheme uses X-rays with photon energy below the K edge of carbon (275–280 eV) that will ionise from the inner valence region. A second probe X-ray at the same energy can excite an electron from the core to fill the vacancy in the inner-valence region. The dynamics of the inner valence hole can be tracked by measuring the Auger electrons produced by the subsequent refilling of the core hole as a function of pump–probe delay. We consider the feasibility of the experiment and include numerical simulation to support this analysis. We discuss the potential for all X-ray pump-X-ray probe Auger spectroscopy measurements for tracking hole migration.